Antioxidant activities, flavonol and flavanol content of selected Southeast Asian indigenous fruits - Santiago, Dennis Marvin O. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2007)
Flavonols and flavanols are known to have antioxidative, antimutagenic, anti-inflammatory and anticarcinogenic effects. This study evaluated the antioxidant potential, total phenolic and flavonoid content, and the flavonol (quercetin, myricetin) and flavanol (catechin, epicatechin) content of fruits of duhat (Syzygium cumini(Linn.) Skeels), kalumpit (Terminalia microcarpa Decna), bignay (Antidesma bunius (Linn.) Spreng) and lipoti {Syzygium polycephaloides (C. B. Robinson) Merr.) which are indigenous to Southeast Asia and widely distributed throughout the Philippines. Results showed that percent non-site-specific scavenging activities of all the fruits were higher than their percent site-specific scavenging activities. Thus, these fruits were better as hydroxyl-radical scavengers than metal chelators. The percent inhibition of linoleic acid peroxidation of duhat, bignay, lipoti and kalumpit were 80.4%, 75.8%, 73.7% and 66.2%, respectively, compared with 85% and 81% for BHT and BHA. Methanolic extracts of duhat, bignay, kalumpit and lipoti were used for the detection of specific flavonols and flavanols. Lipoti and duhat contained 58.85 and 36.55 μg catechin g-1 fresh sample, respectively. Catechin was not detected in kalumpit but it contained 23.42 μg epicatechin g -1 fresh samples. Bignay, on the other hand, was determined to have both catechin and epicatechin with 20.40 and 1.47 μg g-1 fresh samples, respectively. Kalumpit, duhat and bignay also contained 2.73,0.66 and 0.22 μg quercetin g-1 fresh samples, and 5.47, 7.17 and 0.42 μg myricetin g-1 fresh samples, respectively.